THE CHALLENGES FACING GERMAN STUDIES PROGRAMMES IN KENYA: A CASE STUDY OF THE UNIVERSITY OF NAIROBI (The University of Nairobi Journal of Language and Linguistics, 2023)
The German Studies (GS) programme has been offered since 1981 at theUniversity of Nairobi (UoN), 1986 at Kenyatta University (KU), and 2009 atMoi University. By now, the programme should have come of age and beproducing enough language experts and teachers to supply the growingnumber of schools (currently 82) offering German. Available data show thatGS students are so marketable that they are often offered employmentbefore they have completed their university studies. So, the question thatarises is why student enrolments for the subject are not rising accordingly,in particular at the University of Nairobi. This paper discusses answers tothis question and proposes strategies that should be undertaken toincrease student enrolments.